Prenatal diagnosis and selective abortion: a challenge to practice and policy. - Asch, A (1999)
Professionals should reexamine negative assumptions about the quality of life with prenatally detectable impairments and should reform clinical practice and public policy to improve informed decision making and genuine reproductive choice. Current data on children and families affected by disabilities indicate that disability does not preclude a satisfying life. Many problems attributed to the existence of a disability actually stem from inadequate social arrangements that public health professionals should work to change. This article assumes a pro-choice perspective but suggests that unreflective uses of prenatal testing could diminish, rather than expand, women's choices. This critique challenges the view of disability that lies behind the social endorsement of such testing and the conviction that women will or should end their pregnancies if they discover that the fetus has a disabling trait.